1999
DOI: 10.1074/jbc.274.37.26448
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interleukin-1-stimulated NF-κB RelA/p65 Phosphorylation by Mesalamine Is Accompanied by Decreased Transcriptional Activity

Abstract: Nuclear factor B (NF-B) is an inducible transcription factor that regulates genes important in immunity and inflammation. The activity of NF-B is highly regulated: transcriptionally active NF-B proteins are sequestered in the cytoplasm by inhibitory proteins, IB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(133 citation statements)
references
References 33 publications
6
125
1
1
Order By: Relevance
“…Similar to those chemical inhibitors, the natural products mesalamine, mesuol and pertussis toxin appear to specifically block RelA phosphorylation, which is required for optimal RelA-mediated transactivation (Egan et al, 1999;Iordanskiy et al, 2002: Marquez et al, 2005. Moreover, the antiapoptosis protein Bcl-2 was shown to specifically inhibit transactivation by RelA in one study (Grimm et al, 1996), and antithrombin was reported to inhibit NF-kB transactivation by interfering with RelA-CREB co-activator interaction (Uchiba et al, 2004).…”
Section: Inhibitors Of Nf-kb Transactivationmentioning
confidence: 93%
“…Similar to those chemical inhibitors, the natural products mesalamine, mesuol and pertussis toxin appear to specifically block RelA phosphorylation, which is required for optimal RelA-mediated transactivation (Egan et al, 1999;Iordanskiy et al, 2002: Marquez et al, 2005. Moreover, the antiapoptosis protein Bcl-2 was shown to specifically inhibit transactivation by RelA in one study (Grimm et al, 1996), and antithrombin was reported to inhibit NF-kB transactivation by interfering with RelA-CREB co-activator interaction (Uchiba et al, 2004).…”
Section: Inhibitors Of Nf-kb Transactivationmentioning
confidence: 93%
“…[42][43][44] CAPE modifies the NF-kB protein so that it can no longer bind to DNA without any effect on IkBa phosphorylation or IkBa degradation. 31,45 Perhaps, by inhibiting the phosphorylation and degradation of IkBa, degradation of other proteins are also inhibited, whereas the inhibition of NFkB binding to DNA could induce apoptosis. The difference in the NF-kB inhibitor pathway and response to chemotherapyinduced cell death is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The p50-p65 heterodimer binds with a specific sequence in DNA, which in turn results in gene transcription. Phosphorylation of p65 of NF-kB (RelA) is required for effective NF-kB-dependent gene transcription (Egan et al, 1999). In this study, time course-dependent increase or decrease in NF-kB levels in nuclear extracts has been referred to as upregulation or downregulation of NF-kB, respectively.…”
Section: Introductionmentioning
confidence: 99%